THE SEMIOTIC ANALYSIS OF THE LOGOS OF EIGHT JAPANESE CAR COMPANIES IN INDONESIA - VIJAYA, ADIOKA PRAMEDYAS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Semiotic, sign, logo, Japanese car companies. This study analyzed the logo of eight Japanese car companies in Indonesia. There aretwo formulations of the problems which the researcher formulated in this study, namely (1) What is the signifier and signified of Daihatsu, Honda, Isuzu, Mazda, Mitsubishi, Nissan, Suzuki, and Toyota logos? (2) What is the relation between the interpretation of the logo and the company history, marketing or the goal of the company? These problems are answered using the theory proposed by Saussure.This study used a qualitative approach. There are eight Japanese car companies inIndonesia used in this research as data. The reason why researcher using those eight car companies logos, is because those are the famous Japanese car companies in Indonesia.The results of this study have shown the signifier and the signified of eight Japanesecar company logos and the relation between those eight logos and the car company using the theory of semiotic (Sausserean models). The conclusion of this research are (1) Honda, Mazda, Suzuki and Toyota use the first letter of the company name for the logo. Isuzu and Nissan use the whole name of company for the logo whereas Mitsubishi uses symbol for the logo. (2) Although that eight car companies use different sources for the logo eight logos have a relation to the company whether from history, marketing, or the purpose of the company.The researcher hopes, the next researchers who are interested in the analyzing a logo or symbol, use other theories in order to make the analysis better. The next researcher is able to add the theory about Semiotic. Moreover, the next researcher can specifically explain and describe about the sign like symbol logo or anything that can be taken as a sign, for example the meaning of the symbol by using Pierce theory, so that the analysis can be more specific.